2018
DOI: 10.1177/0954410018817688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water ingestion on the tip clearance flow in compressor rotors

Abstract: The tip region of compressor rotors may be filled with water when aircraft is flying in heavy rain environment. In order to explore the effects of water ingestion on the compressor performance and the characteristics of tip clearance flow, the Euler–Lagrange method has been utilized to simulate the two-phase flow inside a transonic rotor (NASA rotor 35). The typical trajectory of water droplet in compressor has been introduced firstly to simply understand the situation of water ingestion and to verify the reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…A large number of flows existing in nature and technology are a mixture of phases, and there are generally three approaches to describe them: the Euler–Euler approach for the continuous fluid multiphase, the Euler–Lagrange approach for a mixture of continuous fluid phase and discrete dispersed phase 25 and the Lagrange–Lagrange approach for the discrete dispersed multiphase. 26,27 The Euler–Euler approach is suitable for the mixing of hot gas jet and cold water and fierce evaporation.…”
Section: Theoretical Basis and Verificationmentioning
confidence: 99%
“…A large number of flows existing in nature and technology are a mixture of phases, and there are generally three approaches to describe them: the Euler–Euler approach for the continuous fluid multiphase, the Euler–Lagrange approach for a mixture of continuous fluid phase and discrete dispersed phase 25 and the Lagrange–Lagrange approach for the discrete dispersed multiphase. 26,27 The Euler–Euler approach is suitable for the mixing of hot gas jet and cold water and fierce evaporation.…”
Section: Theoretical Basis and Verificationmentioning
confidence: 99%
“…It was concluded that as the water content increases, the loss of characteristics increases, the working range is shortened, the flow angle changes, higher clogging occurs in the tip section of the flow and tip losses lead to additional energy losses and performance degradation. Yang and Zhang [8] investigated the effect of incoming water on the performance of a compressor and the characteristics of the tip gap flow. Simulation results show that water droplets change the distribution of airflow parameters along the span direction, leading to a decrease in mass flow velocity and an increase in the angle of attack in the tip region, as well as the separation of the boundary layer at the suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al 21 compared the influence of inlet water spray and tip water spray on the compressor stall boundary and found that both of them can broaden the compressor stall boundary. Yang et al 22 numerically investigated the effect of water ingestion on tip clearance flow in compressor rotors when aircraft is flying in a heavy rain. They found that the unsteady characteristic of tip leakage flow will be amplified, and both the pressure ratio and efficiency of compressor decrease after water ingestion.…”
Section: Introductionmentioning
confidence: 99%